Responsive Local-Needs-Based Policy for Artisanal Small-Scale Gold Mining Control: Case Study in Gunung Mas - Andreastuti, Desie; Afrianti, Pipit (IDFoS Indonesia, 2025)
ABSTRACT Artisanal and Small-Scale Gold Mining (ASGM) in Gunung Mas Regency, Central Kalimantan Province has been a long-standing activity and a vital source of livelihood for much of the local population. However, ASGM practices carried out without adequate regulation have led to various negative impacts, such as environmental degradation, water pollution, land conflicts with local residents, and public health risks. On the other hand, the government’s control policies on ASGM tend to be general and do not fully consider local conditions and needs. This study aims to analyze the extent to which existing policies can respond to the complex problems caused by ASGM at the local level, particularly in Gunung Mas Regency, as well as to explore alternative policy models that are more contextual and participatory. The research uses a descriptive qualitative method with a literature review approach, examining national and regional regulations, previous research reports, and development planning documents. The findings reveal that the implemented policies show minimal responsiveness to local community needs and are mostly top-down in nature. This results in low effectiveness in ASGM control and weak support from local actors. Therefore, it is recommended to develop a more responsive policy model based on active local community participation to create sustainable and equitable ASGM governance.